СТУДЕНТ ЯК СУБ’ЄКТ КУЛЬТУРИ ОСОБИСТІСНОГО САМОВИЗНАЧЕННЯ - Маслюк, Катерина (Збірник наукових праць Уманського державного педагогічного університету, 2020)
Розкрито сутність понять «культура», «самовизначення», «культура самовизначення», «студент як суб’єкт культури». У процесі аналізу наукової літератури встановлено, що культура самовизначення передбачає здатність особистості до здійснення значущих ціннісних виборів, визначення свого місця в різних сферах життєдіяльності, успішність реалізації життєвих планів, встановлення стійких і конструктивних відносин з навколишнім світом. Доведена важливість студента як суб’єкта культури особистісного самовизначення для орієнтації сучасної вищої освіти на задоволення їхньої потреби в самоактуалізації. Раскрыта сущность понятий «культура», «самоопределение», «культура самоопределение», «студент как субъект культуры». На основе анализа научных источников установлено, что культура самоопределения предполагает способность личности к осуществлению значимых ценностных выборов, определения своего места в различных сферах жизнедеятельности, успешность реализации жизненных планов, установление устойчивых и конструктивных отношений с окружающим миром. Доказана важность культуры личностного самоопределения для современных студентов, ориентации высшего образования на удовлетворение их потребности в самоактуализации. Disclosed the essence of the concepts of «culture», «self», «self-culture», «student as the subject of culture». In the analysis of scientific sources revealed that the culture of self-identity provides the ability to exercise significant value election, determining their place in different spheres of life, the success of life plans, the establishment of stable and constructive relations with around the world. Proved culture of personal self-determination for modern students, targeting higher education to meet their needs for self-actualization. The research reveal a problem of self-determination, and there are three interpretations of the concept of «position»: an internal position, life position, personal position. Foreign scientists believe culture is not just a set of ideas, norms, and artifacts, and human interaction that forms living space, which acquire their specific content specific cultural phenomena. That is why a set of internal parameters of each student becoming able to provide just not a subject of culture and culture as a subject of self-determination.